Recent Developments in Improving the Fracture Toughness of 3D-printed Fiber-Reinforced Polymer Composites - Khan, Tayyab; Ali, Murad; Riaz, Zakia; Butt, Haider; Abu Al-Rub, Rashid K; Dong, Yu; Umer, Rehan (Elsevier BV, 2024)
In the past decade, the additive manufacturing of Fiber-Reinforced Polymer Composites (FRPCs) has become an attractive research area. This can be attributed to the ease and versatility of manufacturing, wherein the design of final products takes less time and labor when compared with conventional composite manufacturing techniques. However, due to the inherited nature of the “layer-by-layer” additive manufacturing process, 3D-printed composites are highly susceptible to delamination failure. Continuous efforts are being made in the research community to develop critical techniques involving the optimization of significant printing parameters to enhance the fracture toughness of 3D-printed composite parts toward their structural reliability for different industrial applications. In this comprehensive review, we have discussed the latest developments in improving the mechanical properties and fracture toughness of 3D-printed FRPCs. A holistic review of the properties of low-melting-temperature polymers such as polylactic acid (PLA) and high-melting-temperature polymers like polyetheretherketone (PEEK) based 3D-printed composites is also presented. This paper further covers the effects of changing processing parameters on the fracture toughness of 3D-printed composite structures. These processing parameters comprise printing temperature, printing speed, layer thickness, nozzle geometries, etc., and other key factors influencing the fracture properties of printed parts, such as surface treatment, annealing, and porosity. This is followed by an insightful representation of current challenges, future perspectives, and potential solutions.